Prestación del servicio público de salud durante la pandemia del COVID-19 en el Ecuador. - Cabezas Piedrahita, Víctor Hugo (2021)
The purpose of this academic work is to analyze the responsibility of a State, which unfolds due to the collapse of the public health service, which is provided, in addition to the national health system, through private, autonomous and community entities under the regulation of the national health authority, given the spread of the coronavirus (COVID-19), leading to a medical emergency. With such a state of alteration of the social order, the countries hardest hit by the pandemic have shown problems in the public health service, such as: insufficient protective equipment for health professionals, the exhaustion of hospital beds, the insufficiency of respiratory devices due to the volume of cases diagnosed by the disease and the difficulties in testing the population to identify those infected. Due to so many factors derived from the fragility of the public health system to provide effective care in the fight against the proliferation of the virus and the care of those infected in hospitals, it is imperative to ask: What is the State's responsibility in the face of the COVID-19 pandemic? It is intended to establish the fragility of the public health system in the face of the COVID-19 pandemic, expanding the range of factors that generate the non-contractual liability that entails the Ecuadorian state, whose obligation is to respect and enforce the rights of citizens, seeking to mitigate dissatisfaction and suffering due to the loss of life due to the deficient provision of the referred service.